Paraquat and MPTP alter microRNA expression profiles, and downregulated expression of miR‐17‐5p contributes to PQ‐induced dopaminergic neurodegeneration. Issue 5 (18th December 2017) - Wang, Qingqing; Zhan, Yanting; Ren, Nan; Wang, Zhangjing; Zhang, Qunwei; Wu, Siying; Li, Huangyuan
Abstract: Recent evidence indicates that microRNAs (miRNAs) play a key role in neurodegenerative diseases. However, the toxic effects of paraquat (PQ) and 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP) on miRNA expression profiles in dopaminergic neurons have not been investigated. In the present study, we used microarray analysis to show that PQ and MPTP induce alterations of miRNA expression in neuro‐2a cells. The results reveal that treatment with 300 μm PQ caused miRNA deregulation, such that 60 miRNAs were upregulated and 228 miRNAs were downregulated. Following treatment with 300 μm MPTP, a total of 576 miRNAs were dysregulated, of which 506 were upregulated and 70 were downregulated. Alterations in the expression of miR‐17‐5p, miR‐210‐3p, miR‐374‐5p, miR‐378‐3p and miR‐503‐5p were verified by real‐time quantitative reverse transcriptase polymerase chain reaction. Moreover, overexpression of miR‐17‐5p in Neuro‐2a cells enhanced cell proliferation, suppressed apoptosis and promoted S phase transition of the cell cycle after PQ treatment. Taken together, our study demonstrates that characteristic changes in miRNA expression profiles occur after PQ and MPTP treatment, which suggests that miRNAs may be involved in the development of PQ‐ and MPTP‐induced neurodegeneration. Downregulated miR‐17‐5p expression contributes to PQ‐induced dopaminergic neurodegeneration. Abstract : Recent evidence indicates that microRNAs (miRNAs) play a key role in neurodegenerative diseases. However, the toxic effects of paraquat (PQ) and 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP) on miRNA expression profiles in dopaminergic neurons have not been investigated. In the study, we demonstrate that characteristic changes in miRNA expression profiles occur after PQ and MPTP treatment, which suggests that miRNAs may be involved in the development of PQ‐ and MPTP‐induced neurodegeneration. Downregulated miR‐17‐5p expression contributes to PQ‐induced dopaminergic neurodegeneration.